2022
DOI: 10.1109/tro.2021.3086632
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Redundancy to Facilitate Physical Interaction

Abstract: The control of kinematically redundant robots is often approached using nullspace projection, which requires precise models and can be computationally challenging. Humans have many more degrees of freedom than are required to accomplish their tasks, but given neuro-mechanical limitations, it seems unlikely that biology relies on precise models or complex computation. An alternative biologically-inspired approach leverages the compositionality of mechanical impedance. In theory, nullspace projection eliminates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 82 publications
(97 reference statements)
0
18
0
Order By: Relevance
“…However, redundant degrees of freedom may be controlled by superposition of mechanical impedance primitives. Remarkably, unlike optimization-based methods, as the number of redundant degrees of freedom increased, control based on the superposition of impedance primitives improved; in effect, with greater redundancy control became easier [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, redundant degrees of freedom may be controlled by superposition of mechanical impedance primitives. Remarkably, unlike optimization-based methods, as the number of redundant degrees of freedom increased, control based on the superposition of impedance primitives improved; in effect, with greater redundancy control became easier [38].…”
Section: Discussionmentioning
confidence: 99%
“…By comparing (11) and (12) with the passivity condition of (10), and considering the boundedness of U g (q), it can be concluded that the controller is strictly output passive with respect to the interaction port ( q, −τ imp ).…”
Section: B Passivity Property Of the Controller For Passive Environmentsmentioning
confidence: 99%
“…This has the consequence that the desired endeffector behavior might suffer. It was shown in [10] that the conflict can be minimized if the robot has enough DOF.…”
mentioning
confidence: 99%
“…, the initial guess of the independent coordinates for the high-fidelity HAMM, is given by ind s init = K qq (6) where K is a sparse matrix given by 44 1 1 11…”
Section: Hybrid Ik Algorithmmentioning
confidence: 99%
“…In such case natural human arm postures have to be replicated autonomously. This challenge mainly results from the redundant degrees of freedom (DoFs) and unknown postural control strategy of human arms [6].…”
Section: Introductionmentioning
confidence: 99%